KAJIAN SISTEM BUKAAN KAMAR TIDUR ASRAMA BEIYUAN GXNU TERHADAP KENYAMANAN TERMAL DAN PENCAHAYAAN ALAMI RUANG - CITRA AMELIA (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2016)
Dormitory played an important role on university students life. Lot of universities oblige their students to live inside universityâ€™s dormitory with consideration that that thing would make observing students activities easier. Dormitory bedrooms comfort were crucial. This because of bedroom was the place where students would comeback to get a good rest after their daily activities outside. One of many things that could determine one rooms comfort was apertures design. Apertures design would affect a room wind circulation. Aside from natural circulation, apertures would determine the intensity of natural lighting that can get into the room. Â Keywords: climate; lighting; students activity; temperature